Numerical analysis and experiment of sandwich T-joint structure reinforced by composite fasteners - Guo, Shijun; Li, Wenhao (Elsevier, 2020)
This study presents an investigation into the failure mechanism and strength improvement of a sandwich composite T-joint bonded and reinforced by fasteners made of thermoplastic composite. The T-joint subjected to pulling load was analysed by numerical simulation and experiment methods. Cohesive zone model (CZM) and Hashin damage model were used in the FE analysis to simulate the crack propagation and composite fastener damage. According to the results, the composite joint reinforcement is mainly attributed to the resistance of composite fasteners to shear failure of the bonded interface. Following the interface delamination and crack propagation in mode II failure, fracture of the composite fasteners occurred in transverse shear mode. The results show nearly 19% increase of bonding strength for the T-joint reinforced by composite fasteners of 5 mm diameter compared to the T-joint without fasteners. After the interface delamination, pull-out failure of fasteners was also observed and correlated to the numerical model considering material property reduction due to the sparse fibre tows in the fastener head forming and T-joint assembly. The investigation was extended to a parametric study of diameter and fibre orientation of the composite fasteners. The results show that the T-joint reinforced by composite fasteners of 6.28 mm diameter and lay-up can achieve the same strength and 44% weight saving compared to a titanium fastener opponent of 5 mm diameter.
Keywords: Sandwich composite T-joint; Composite fastener; Mechanical testing; Failure mechanism